Effect antioxidants application on microshear bond strength of universal adhesive to bleached enamel - Machado, Ana Luiza; Nascimento, Dayana; Coelho Junior, Paulo; França, Fabiana; Turssi, Cecilia; Basting, Roberta; Amaral, Flávia Lucisano Botelho (Brazilian Dental Science, 2020)
Purpose: To evaluate, in vitro, the influence of antioxidants (green tea extract - GT and sodium ascorbate - SA) on microshear bond strength (?SBS) of a universal adhesive system – self-etching mode (UAS) to bleached enamel. Material and Methods: After obtaining 50 fragments of human dental enamel (4 mm x 4 mm), forty fragments were submitted to at-home bleaching technique using 10% carbamide peroxide (Opalescence PF, Ultradent) for two hours/day, for four weeks. They were randomly divided in four groups (n=10): GT - 10% aqueous GT solution (60 minutes); SA - 10% SA solution (10 minutes); Negative control - no antioxidant agent, immediately restored; PC1 (positive control 1) - no antioxidant agent, restored 14 days the bleaching procedure. Ten enamel fragments were assigned to PC2 group (positive control 2), in which the adhesive procedures were realized in non-bleached enamel. The UAS (Adper Single Bond Universal, 3M ESPE) was applied on enamel surface according to manufacturer’s instructions and two cylinders (0,8 mm diameter) of nanoparticulate composite resin (Z350, 3M ESPE) were made on each sample. After 24 hours, the cylinders were submitted to ?SBS in a universal test machine (0.5 mm/min). Fracture mode was evaluated in stereomicroscope (40x magnification). SBS data, in MPa, was submitted to one-way ANOVA (?=0,05). Results: There was no statistical difference between the experimental groups (p=0,545). The fracture mode demonstrated that there was predominance of adhesive fracture in all groups. Conclusion: Neither the bleaching procedure nor the application of antioxidants to bleached enamel interfered in the bond strength of the tested universal adhesive system. KEYWORDS Antioxidants; Dental bleaching; Shear strength.